The effect of drought stress on Pinellia ternata in terms of physiology and aquaporin genes after Arbuscular mycorrhizal fungal inoculation - Shuang Li; Yajun Liu; Han He; Yike Xu; Xiaochun Sun; Wenjing Huang (Journal of Applied Botany and Food Quality)
Pinellia ternata (P. ternata) is a traditional Chinese herbal medicine. Arbuscular mycorrhizal fungi (AMF) establish symbiosis with plants, which is essential in improving mineral nutrient acquisition and drought resistance of host plants. This study used the medicinal plant P. ternata as the experimental material to investigate the similarities and differences in photosynthesis, osmotic regulation, and antioxidant activity between arbuscular mycorrhizal and non-arbuscular mycorrhizal plants under drought stress. The results showed that AMF inoculation could significantly increase the photosynthetic rate (Pn), stomatal conductance (Gs), and transpiration rate (Tr) of P. ternata. Under drought stress, P. ternata adapted to drought by accumulating osmotic regulatory substances such as proline and soluble proteins and increasing chlorophyll content. In addition, Mycorrhizal P. ternata also exhibited high activities of peroxidase, superoxide dismutase, and catalase under drought conditions, improving the response of the antioxidant system. AMF could promote the growth and development of P. ternata under drought stress. Mycorrhization upregulated the expression of PtTIP, NIP, and PIP genes under drought stress. AMF can alleviate drought stress-induced damage by regulating photosynthetic capacity, osmosis, antioxidant activities, and aquaporin gene expression. Our study highlights the effect of AMF on P. ternata under drought stress by mediating physiological and biochemical activities.